Penyelesaian Yuridis Tentang Penyadapan sebagai Bagian dari Kegiatan Spionase yang Dikategorikan dalam Pelanggaran Kekebalan Diplomatik - Dita Birahayu (Perspektif Hukum, 2015)
In international relations conducted between states, countries sending delegates to negotiate with other countries in order to promote and safeguard their interests in addition to work towards the common good. Many disorders that can occur in the case of countries conduct cooperation with other countries and can not be separated from the conflict, one of which is the treatment or unpleasant activities of the recipient countries where diplomatic representation is placed. As one example of the violation of diplomatic immunity and privileges of officials is espionage case between Indonesia and Australia that occurred some time ago. This is the case, then the sending country may submit an objection to the recipient (receiving state) and the receiving country shall be fully responsible for it. This paper will discuss how the settlement of juridical acts of espionage to diplomatic officials as a violation of diplomatic immunity.